Strategi Pengembangan BUMG dalam Meningkatkan Pendapatan Gampong Pasar Aceh Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Silvi Yanti, Fitri; Wahyu Handayani, Sri (Indonesian Journal Publisher, 2023)
This research aims to examine how the strategy for developing Village-Owned Enterprises (BUMG) in Gampong Pasar Aceh achieves the objectives of each program to increase village origins (PAG), and to find out what obstacles are faced in each program implemented. implemented in Gampong Pasar Aceh in order to increase village income. The type of research used is qualitative research with a descriptive approach. The location of this research was carried out in Pasar Aceh village. Johan Pahlawan District, West Aceh Regency. Data collection techniques use interview techniques, documentation and field observation. Informants in this study used a purpove sampling technique, namely the sample was addressed to (the village head of Pasar Aceh, head of finance, director of Pasar Aceh and 7 people in the community). The results of this research indicate that gampong development in Pasar Aceh has been good in terms of increasing gampong income, seen from 3 development strategy indicators, namely: (1) Organizational strategy through the vision and mission of developing new markets; (2) Strategic resource support is seen in 4 dimensions, namely facilities and infrastructure, natural resources, human resources and financial resources; (3) strategic programs, namely implicit programs in organizations and implicit programs in society. However, behind the development of new market BUG, there are obstacles in management activities, such as weather factors, budget limitations so that they cannot maximize the use of funds for program needs, and a lack of human resources in financial management.